TRICYCLIC ANTI-DEPRESSANT INDUCED MANIA - Sethi, B. B. (Medknow Publications, 1980)
The authors report four cases of Monopolar Depressed patients who developed manic features for the first time while on tricyclic antidepressant therapy. The phenomenon is viewed as tricyclic antidepressant induced mania. The manic symptoms occurred late in therapy, with moderate doses of tricyclic antidepressants (125-150 mg per day) and were easily controlled with antipsychotic medication. Factors relating to age of patients, metabolic products of tricyclic antidepressants and central nor-adrenergic and dopaminergic systems are considered important and their role has been discussed.